A fatal case of fulminant myocarditis caused by influenza A virus - Kovačević, Mila Radmila; Srdanović, Ilija; Jaraković, Milana; Bogdanović, Dragana; Samardžija, Golub; Čanković, Milenko (Vojnosanitetski pregled, 2021)
Abstract Introduction. Myocarditis is defined as an inflammation of a heart muscle, which can be caused by a number of agents, among which viruses are the most common. Fulminant myocarditis is a rapidly progressive, life-threatening myocarditis, followed by the development of cardiogenic shock. Among viruses, there are a number of common ones, but according to our knowledge, there are only a few cases of fulminant myocarditis caused by influenza A virus described in the literature. Case report. We presented a 44-year-old man who was admitted to the Cardiology Intensive Care Unit because of the clinical as well as electrocardiographic signs pointing to the ST-segment elevated myocardial infarction with peracute development of heart failure and cardiogenic shock and subsequently lethal outcome, despite applied circulatory support. The urgent coronarography showed no signs of coronary artery disease, while the autopsy revealed myocarditis and the real-time polymerase chain reaction of nasopharyngeal swab revealed influenza A(H3) virus. Conclusion. Fulminant myocarditis is a life-threatening cardiac disease which should be treated in Intensive Care Units with both medicament and mechanical circulatory support and antiviral therapy and which, despite the applied therapy, has a high mortality rate. Influenza A virus is a rare cause of fulminant myocarditis which should be taken into consideration.